Dual role of bacteria in Pine Wilt Disease. - Vicente, Cláudia (2012)
Pine wilt disease (PWD) is one of the most serious problems in pine forests, and also one of the most serious biological invasion issues worldwide. The causal agent, the pinewood nematode (PWN), Bursaphelenchus xylophilus, is considered to have its center of origin in North America, where it has co-evolved for millions of years, and is in balance with the autochthonous pine species. The PWN was firstly described as the casual organism of PWD in 1971. Later, in 1980, a possible involvement of toxin producing-bacteria in association with B. xylophilus in PWD was hypothesized. Ever since, efforts have been made to unravel the role(s) of bacteria in PWD. Preliminary results show that bacteria associated with B. xylophilus can induce PWD, although the symptoms shown by the plant host are slightly different from those observed when the nematode is inoculated alone. These observations suggest that bacteria can act in a different pathway than the pinewood nematode. It has been hypothesized that toxin producing-bacteria can lower plant defense systems, thus helping nematode infection and proliferation in the plant host. If so, how, where and when do bacteria act? Which mechanisms are utilized? These questions remain unanswered. Still the role of bacteria in PWD seems to be evident. Interestingly, a solution for this disease can also involve the bacteria. The use of plant growth promoting bacteria (PGPB) is already known to be a useful tool in helping plant host overcome several biotic stresses, including pathogen attack. In this sense, bacteria may present a dual role in the complex system of the PWD.